Efficient Inactivation of Symbiotic Nitrogen Fixation Related Genes in Lotus japonicus Using CRISPR-Cas9 - Wang, Longxiang; Wang, Longlong; Tan, Qian; Fan, Qiuling; Zhu, Hui; Hong, Zonglie; Zhang, Zhongming; Duanmu, Deqiang (Frontiers in Plant Science, 2016)
The targeted genome editing technique, CRISPR/Cas9 system, has been widely used to modify genes of interest in a predictable and precise manner. In this study, we describe the CRISPR/Cas9-mediated efficient editing of representative SNF (symbiotic nitrogen fixation) related genes in the model legume Lotus japonicus via Agrobacterium-mediated stable or hairy root transformation. We first predicted nine endogenous U6 genes in Lotus and then demonstrated the efficacy of the LjU6-1 gene promoter in driving expression of single guide RNAs (sgRNAs) by using a split yellow fluorescence protein (YFP) reporter system to restore the fluorescence in Arabidopsis protoplasts. Next, we chose a customized sgRNA targeting SYMRK (symbiosis receptor kinase) loci and achieved ~35% mutagenic efficiency in 20 T0 transgenic plants, two of them containing biallelic homozygous mutations with a 2-bp deletion near the PAM region. We further designed two sgRNAs targeting three homologous leghemoglobin loci (LjLb1, LjLb2, LjLb3) for testing the possibility of generating multi-gene knockouts. 20 out of 70 hairy root transgenic plants exhibited white nodules, with at least two LjLbs disrupted in each plant. Compared with the constitutively active CaMV 35S promoter, the nodule-specific LjLb2 promoter was also effective in gene editing in nodules by hairy root transformation. Triple mutant knockout of LjLbs was also obtained by stable transformation using two sgRNAs. Collectively, these studies demonstrate that the CRISPR/Cas9 system should greatly facilitate functional analyses of SNF related genes in Lotus japonicus.